Testing wastewater from a music festival in Switzerland to assess illicit drug use. (April 2020) - Benaglia, Lisa; Udrisard, Robin; Bannwarth, Anne; Gibson, Aline; Béen, Frederic; Lai, Foon Yin; Esseiva, Pierre; Delémont, Olivier
Highlights: Wastewater analysis shows that cocaine, MDMA and amphetamine use is stable over two editions of a Swiss music festival. Wastewater analysis confirms that MDMA is internationally prevalent in festivals, as well as amphetamine to a lesser extent. MDMA and amphetamine are more consumed during the festival compared to normal times, when there is no festival. Police seizures supports the hypothesis of an existing market for MDMA and amphetamine during the festival. Abstract: This article describes the application of a recently proposed framework for deploying wastewater-based epidemiology (WBE) to monitor illicit drug use within festivals (Benaglia et al., 2019). The festival under study was a week-long music festival in Switzerland (Swiss Festival) which attracted around 50, 000 people daily. Wastewater sampling was performed during its 2014 and 2015 editions. As the Swiss Festival's wastewater is conveyed to the sewage treatment plant (STP) of the nearby city, to assess illicit drug use when there is no festival (i.e. the background consumption) wastewater sampling was also carried out during an off-festival week in 2015. During the 2014 and 2015 editions of the Swiss Festival, WBE highlighted that the most consumed illicit drugs were cannabis, MDMA, cocaine and amphetamine. Excluding cannabis, the means per capita loads of all illicit drugs were not statistically different between both editions of the Swiss Festival. The results were then compared to those of an Australian festival which had also been subject of a quantitatively assessed illicit drug use study (Lai et al., 2013). This comparison confirmed that MDMA is highly prevalent, as well as amphetamine, although to a lesser extent. Consumption of cocaine (in Switzerland) and methamphetamine (in Australia) is also high, but their use seems to be related to their availability (i.e. to the country where the festival takes place). Furthermore, it was observed that MDMA and amphetamine are more consumed during the festival compared to normal times, when there is no festival. This might suggest that their availability is increased and therefore, that a market for these substances potentially exists during the festival. This last hypothesis was assessed by consulting drug seizures made by the police during the 2015 Swiss Festival. Despite very limited data, police records suggested that most of the drugs were purchased at the festival, which supports the previous hypothesis. Results validate, on the one hand, WBE as a useful indicator to monitor illicit drug use within festivals and on the other hand, the suggested framework for deploying WBE in such environment. In addition, this study suggests the need for prevention and harm reduction measures targeted on MDMA and amphetamine during the Swiss Festival, such as drug checking laboratories.